Pemberdayaan Kesehatan Masyarakat Melalui Seminar Pencegahan Stunting di Desa Bangunrejo Kabupaten Kendal - Nikmatur Rohmah; Erik Ade Riza; Fazira Avanza; Aang Asari (Lembaga Pengembangan Kinerja Dosen, 2024)
The health seminar is one of the work programs of UIN Walisongo Semarang community service students (KKN), designed and presented during the work program seminar, and later implemented during KKN activities. The seminar aims to provide insights to the community, especially in Bangunrejo Village, about stunting and its prevention efforts. The target audience includes mothers of toddlers and village health cadres in Bangunrejo Village, chosen due to the lack of awareness among residents about stunting and its prevention. The seminar was held on Monday, August 13, 2024 ,and utilized a counseling method in the form of a seminar with the theme